Evaluation of the Multiple Micronutrient Supplement (MMS) program to prevent anemia in pregnant women at public health center x - Adib Maulana Pratama; Vanessa Zaskia Putri; Siti Purwitasari; Nasya Andini Wahda; Era Febriana Rahmadhani; Teguh Irawan; Yulis Indriyani (Indonesian Journal of Health Science, 2026)
Anemia in pregnant women remains a significant health issue that requires attention, as it can affect the health of both the mother and the fetus. In the service area of the X Community Health Center, the prevalence of anemia among pregnant women remains quite high, necessitating effective preventive measures, one of which is the Multiple Micronutrient Supplementation (MMS) program. This study aims to evaluate the implementation of the MMS program in preventing anemia among pregnant women at the X Community Health Center. The study employed a qualitative method using the Input, Process, and Output (IPO) evaluation approach. The input aspects examined included policies, human resources, facilities and infrastructure, logistics, funding, and the knowledge of pregnant women. Process aspects included MMS administration, education, consumption compliance, monitoring, side effects, and family support, while output aspects included MMS coverage, changes in pregnant women’s hemoglobin levels, perceived benefits, and satisfaction among pregnant women. The primary informants in this study were 10 pregnant women in the service area of the X Community Health Center, while the triangulation informants consisted of 2 health center staff members from the X area who were selected using purposive sampling. Data were collected through in-depth interviews and analyzed thematically. The results of the study indicate that the MMS program is functioning fairly well, with a consistent supply of supplements and easily accessible services. However, challenges remain, including the absence of specific standard operating procedures (SOPs), suboptimal compliance monitoring, and uneven education. Therefore, improvements are needed in monitoring, record-keeping, and education so that the MMS program can operate more effectively in helping to prevent anemia in pregnant women.